2021
DOI: 10.1182/bloodadvances.2021005357
|View full text |Cite
|
Sign up to set email alerts
|

Dose Finding Study of Ibrutinib and Venetoclax in Relapsed or Refractory Mantle Cell Lymphoma

Abstract: Relapsed Mantle cell lymphoma (MCL) is often treated with Bruton's Tyrosine Kinase inhibitors (BTKi); however, post-BTKi relapse can be challenging. Adding venetoclax (VEN) to ibrutinib(IBR) has shown synergy in pre-clinical MCL models. Prior MCL studies of the combination report promising efficacy but have conducted limited dose finding. We sought to identify the optimal dosing combination, based on efficacy and toxicity, utilizing a continual re-assessment method of 6 combinations of IBR (280mg, 420 mg, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Utilizing a continued reassessment method, the findings showed an optimal dose of ibrutinib of 420 mg daily, with venetoclax at 200 mg daily, which is lower than the doses used in the AIM or SYMPATICO trials. Despite the lower doses, the ORR of 83% and a CR rate of 42% were comparable to prior trials [ 45 ].…”
Section: Beyond Btk Inhibitors: Targeted Therapiessupporting
confidence: 80%
“…Utilizing a continued reassessment method, the findings showed an optimal dose of ibrutinib of 420 mg daily, with venetoclax at 200 mg daily, which is lower than the doses used in the AIM or SYMPATICO trials. Despite the lower doses, the ORR of 83% and a CR rate of 42% were comparable to prior trials [ 45 ].…”
Section: Beyond Btk Inhibitors: Targeted Therapiessupporting
confidence: 80%
“…Considering the optimal dosing arm in isolation, neither median PFS or OS had been reached with a median follow up of 22.9 months in this subgroup. [74] However, firm conclusions on response and survival rates should be made with caution in this study, given the fixed duration of therapy at only 6 cycles, variability in dosing and relatively small cohort size within dose levels. Additionally, the study selected for patients with lower risk MCL when compared to previous trials and those who had received a previous BTKi were excluded.…”
Section: Venetoclax and Ibrutinibmentioning
confidence: 91%
“…Recently Portell and colleagues published results from their effort to further refine the dosing strategy of venetoclax plus ibrutinib, and mitigate the toxicity shown in AIM and the SYMPATICO SRI cohort; hypothesising that lowering the dose used in single-agent strategies might achieve a better balance between efficacy and toxicity. [74] In this trial, venetoclax was commenced first, with ibrutinib incorporated during the venetoclax dose ramp-up, and a continual reassessment method (CRM) was employed to identify the optimal combination of doses, from 6 different dose permutations.…”
Section: Venetoclax and Ibrutinibmentioning
confidence: 99%
“…These observations support the use of time-limited combination regimens which may remove the sustained selection pressure for BCL2- mutated subclones, and indeed, no BCL2 mutations have been detected among patients treated with time-limited therapy to date. Concomitant BTK inhibition may subvert the upregulation of alternative BCL2 family proteins by the tumor microenvironment, and combination trials have demonstrated frequent deep remission in CLL and MCL [ 29 , 78 , 149 , 150 ]. Further investigation is ongoing into the clinical development of BCL-X L and MCL1 inhibitors to eradicate venetoclax-resistant subpopulations and hopefully enhance the curative potential of BH3-mimetic-based regimens [ 24 ].…”
Section: Associations and Mechanisms Of Resistance To Pro-apoptotic A...mentioning
confidence: 99%